(3GdahGFO GdTfThQjI aj TQM GdefXheI GdQMHjIs - (3GdTfThQj GdYLej GdeUQj, GdNWjH, YHO Gddg Hf eMeO Hf YHO Gddg, J (B999 (3g`s ((3Ydj Hf MSf GdfKQJj GdeGdcj GdCRgQjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hHYO ajbhd YHO Gddg GdTfThQj bO SCdfj hdOj YHO GdhgGH Cf CTQM dg GdefRheI GdQMHjI aCLHJg dPdc hSejJg GdahGjO GdTfThQjIs
(3BNQgG (B:s
(3aYdjg HcJGHfG TQM GdJQJjH jXaQ HeG jQjO aEfg cJGH jZfj Yf cJH cKjQI aj Pdcs
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B984 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 128s
(3eYLe GdeDdajf (B2 / 285s
(3EjVGM Gdecfhf (B2 / 207s
(3gOjI GdYGQajf (B1 / 473s
Keywords: (3GdaQGFVs